PENGARUH EKSTRAK BUAH JAMBLANG TERHADAP KADAR ANTOSIANIN, AKTIVITAS ANTIOKSIDAN DAN SIFAT ORGANOLEPTIK ES KRIM UBI UNGU - Ramzy Arif Satriyo Bima Anggara (2021)
Diabetes mellitus (DM) is a metabolic disease characterized by chronic high blood sugar levels (hyperglycemia) due to abnormalities in insulin secretion or insulin action. Free radicals can trigger oxidative stress which induces insulin resistance in peripheral tissues and destroys insulin secretion from pancreatic beta cells resulting in type 2 diabetes. Jamblang fruit is a food ingredient that has high anthocyanin levels which are useful for reducing free radical compounds. The purpose of this study was to analyze the effect of jamblang fruit extract substitution on anthocyanin levels, antioxidant activity and organoleptic properties of purple sweet potato ice cream, to determine the selected formula, and to determine the nutritional content of the selected formula. This research is an experimental study with a one-factor completely randomized design (CRD) with two repetitions. The formulations were divided into 3 with respective percentage levels of substitution of jamblang fruit extract of F1 (30%), F2 (40%), F3 (50%). The results of the analysis showed that the level of jamblang fruit extract substitution had a significant effect (p = 0.000) on the level of preference for panelists on color parameters and had no significant effect (p> 0.05) on the level of preference for panelists on aroma, taste and texture parameters. Based on the anthocyanin content test, the substitution of jamblang fruit extract had a significant effect (p <0.05) on the anthocyanin levels of purple sweet potato ice cream. Based on the antioxidant activity test, the substitution of jamblang fruit extract had a significant effect (p <0.05) on the antioxidant activity of purple sweet potato ice cream. The selected formula is F3 purple sweet potato ice cream with 50% substitution of jamblang fruit extract containing 52.42 kcal of energy, 1.83 grams of protein, 0.72 grams of fat, 9.6 grams of carbohydrates, 87.42% moisture content, ash content. 0.39%, anthocyanin levels (208.63 ± 0.7205 mg / L), and antioxidant activity (4365 ± 0.756 ppm)